2004
DOI: 10.1116/1.1767197
|View full text |Cite
|
Sign up to set email alerts
|

Mn and Be codoped GaAs for high hole concentration by low-temperature migration-enhanced epitaxy

Abstract: We report the effect of codoping of Mn–Be and the modified doping on an increment of the total hole concentration. Both the Mn-doped and Be-doped samples exhibit hole concentrations higher than 1×1019 cm−3 at room temperature. In contrast, the Mn–Be codoped sample shows a remarkable decrease in its hole concentration and mobility. Therefore, the resistivity is increased by more than 102 times of the Be-doped sample. This dramatic deterioration is probably caused by the complex defects due to the codoping. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…These point defects often act as a hole killer in Mn-doped GaAs. Therefore, some additional doping of acceptor impurity is needed to achieve a high hole concentration, and co-doping of Mn with the other p-type impurity such as Be has been attempted [10,14]. However, the results of all these works were quite disappointing; it has been found that the Mn-Be co-doping in GaAs deteriorates the hole concentration considerably.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…These point defects often act as a hole killer in Mn-doped GaAs. Therefore, some additional doping of acceptor impurity is needed to achieve a high hole concentration, and co-doping of Mn with the other p-type impurity such as Be has been attempted [10,14]. However, the results of all these works were quite disappointing; it has been found that the Mn-Be co-doping in GaAs deteriorates the hole concentration considerably.…”
Section: Introductionmentioning
confidence: 96%
“…The observed hole concentration is even lower than the values of Mn or Be solely doped samples. This dramatic deterioration is probably caused by the complex defects due to the co-doping [14]. Yu et al [10,12] reported that the concentration of Mn interstitials and Mn-related clusters increases with increasing Be concentration.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, it is necessary to decrease the interstitial Mn to increase the hole concentration and the Curie temperature. In our previous study, spatially separated doping (SSD) was applied to GaMnAs, and high hole concentrations have been achieved [5,6]. Magnetic properties of GaMnAs have also been improved by using SSD.…”
Section: Introductionmentioning
confidence: 97%
“…Another approach to obtaining higher Curie temperatures is to increase hole concentration by additional p-type doping. We have demonstrated the co-doping in uniform 13) and spatially separated 14) structures by introducing Be, which is conventionally used for p-type dopants in GaAs. Magnetic properties are improved by employing the spatially separated doping technique since hole concentration is successfully increased by additional Be without the formation of Mn-Be complex defects.…”
Section: Introductionmentioning
confidence: 99%